2009
DOI: 10.2174/1874285800903010001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Human CD4+ T Lymphocytes via TLR3, TLR5 and TLR7/8 Up-Regulates Expression of Costimulatory and Modulates Proliferation

Abstract: The cells of innate and adaptive immunity, although activated by different ligands, engage in cross talk to ensure a successful immune outcome. Toll-like receptors (TLRs) are key components of the innate immune system and have the ability to detect microbial infection and trigger host defence responses. Otherwise, human T lymphocytes are able to produce most TLRs. Thus, we analyze the capability of some TLR ligands to modulate the function of highly-purified CD4+ T cells. We found that agents acting via TLRs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…To date, the effects of R848 on T cell proliferation have mainly been investigated in the human system. R848 is able to induce T cell proliferation and activation of human CD4 + T cells (34); however, in MLRs, T cell proliferation was reduced after R848 application (35). In our in vivo system, proliferation of Ag-specific CD4 + T cells was likewise reduced suggesting that despite increased IFN-g, IFN-a, IFN-b, IL-12p35, IL-12p40, and KC in comparison with unsensitized but OVAchallenged controls is shown.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…To date, the effects of R848 on T cell proliferation have mainly been investigated in the human system. R848 is able to induce T cell proliferation and activation of human CD4 + T cells (34); however, in MLRs, T cell proliferation was reduced after R848 application (35). In our in vivo system, proliferation of Ag-specific CD4 + T cells was likewise reduced suggesting that despite increased IFN-g, IFN-a, IFN-b, IL-12p35, IL-12p40, and KC in comparison with unsensitized but OVAchallenged controls is shown.…”
Section: Discussionmentioning
confidence: 56%
“…For intracellular cytokine analysis, we used allophycocyanin-labeled IFN-g (BD Pharmingen), PE-labeled IL-17A (BD Pharmingen), and PE-labeled IL-5 (BD Pharmingen). Abs were incubated at 4˚C for [30][31][32][33][34][35][36][37][38][39][40] ), single-cell suspensions of tracheal lymph nodes or lung cells were adjusted and surface stained for PeCy7-labeled CD4 PeCy7 and PE-labeled CD25 (all BD Pharmingen) as described. Foxp3 staining was performed following the advice of the manufacturer of the fixation/permeabilization set (eBioscience).…”
Section: Assessment Of Intracellular Cytokine Staining and Regulatorymentioning
confidence: 99%
“…As some studies previously demonstrated, direct TLR triggering on CD4 ϩ T cells can induce up-regulation of costimulatory molecules and modulate their proliferation. 48,49 Nevertheless, it has been demonstrated that the most effective multifunctional CD8 ϩ T-cell response is induced when the antigen is fused to the adjuvant, rather than delivered separately, 46 a finding that might explain the lack of CD8 ϩ T-cell responses in melanoma patients vaccinated with NY-ESO and topical TLR7 agonist. 50 Thus, our own data support the approach of conjugating TLR agonists to a targeting antigen vaccine, such as DCIR, as the most efficient method to deliver an antigen and adjuvant directly to DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies by others have shown costimulation of CD4+ T cells by dsRNA and LPS that are ligands of TLR3 and TLR4, respectively (Caramalho et al 2003;Gelman et al 2004). A recent study investigated the direct effects of TLR3, 5 and 7 ligands in regulating expression of costimulatory molecules on human peripheral CD4+ T cells (Simone et al 2009). Interestingly, stimulation of purified CD4+ T cells by each of the three (TLR3, 5 and 7) ligands resulted in reduced CD28 expression by 72 h poststimulation with a concurrent up-regulation of CD152 and PD-1 expression that inhibited further T cell proliferation and activation.…”
Section: Tlr-costimulation In Cd4+ T Cell Responsesmentioning
confidence: 99%